2016
DOI: 10.12659/pjr.899221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Posterior Superior Alveolar Artery Using Cone Beam Computed Tomography

Abstract: SummaryBackgroundMaxillary posterior tooth region is an important area with respect to periapical surgery, implant placement, and sinus lifts. Posterior superior alveolar artery (PSAA) is located on the lateral wall of maxillary sinus and may become injured during such surgical procedures. Therefore, knowledge of the subject is essential to a clinician.The goal was to determine the anatomical relationship of posterior superior alveolar artery to the floor of maxillary sinus and alveolar crest.In our study we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 15 publications
6
31
2
2
Order By: Relevance
“…The diameter of PSAA was measured between 0.63 ± 0.38 and 1.24 ± 0.18 mm in the literature. 22,23 In accordance with the literature, the PSAA diameter in first premolar, second premolar, first molar, and second molar regions were measured 0.97, 0.88, 0.9, and 0.94 mm, respectively. Almost in all studies, the most frequent PSAA localization was classified as intraosseous.…”
Section: Discussionsupporting
confidence: 72%
“…The diameter of PSAA was measured between 0.63 ± 0.38 and 1.24 ± 0.18 mm in the literature. 22,23 In accordance with the literature, the PSAA diameter in first premolar, second premolar, first molar, and second molar regions were measured 0.97, 0.88, 0.9, and 0.94 mm, respectively. Almost in all studies, the most frequent PSAA localization was classified as intraosseous.…”
Section: Discussionsupporting
confidence: 72%
“…The reason as to why CBCT results are higher than the CT results may be due to the higher resolution of CBCT, the specialization and/or experience of the examiners, the methodology applied, and whether dentulous or edentulous patients are included in the study as well as sample size. 25,28,29…”
Section: Discussionmentioning
confidence: 99%
“…Güncü et al 24 detected that this distance was 7.8 ± 0.3 mm. Pandharbale et al 28 stated that the distance between the PSAA canal/notch and the floor of the maxillary sinus in the left first and second molar regions was 10.48 ± 3.21 mm and 9.49 ± 3.12, respectively, and was shortest in the second molar region. In this study, the mean distance from the PSAA to the floor of the sinus was 9.54 ± 4.27 mm at the FDP and 7.91 ± 4.75 mm at the LDP.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT studies showed that PSAA was detected in 61 to 87% of the patients; it was located underneath the mucosa in 22% to 47% (type I), intraosseus in 47% to 73% (type II) and external cortex (superficial) in 5% to 6% (type III), and the mean diameter of the PSAA was 0.63 mm to 1.37 mm [29303132]. According to Khojastehpour et al [33], the rate of the detection rate of the PSAA in patients with an alveolar ridge height of <10 mm was significantly greater than the rate of detection in patients with an alveolar ridge height of >10 mm.…”
Section: Imagingmentioning
confidence: 99%